The Impact of FDI on Economic Growth An Analysis for the Transition Countries of Central and Eastern Europe - Neuhaus, Marco. (Contributions to Economics,, 2006)
This book provides a comprehensive understanding of the relationship between FDI and economic growth with special attention to the countries of Central and Eastern Europe. Within a new semi-endogenous growth model, the book illustrates the impact of FDI on economic growth for every stage of development of a country. Developing countries experience both strong capital accumulation and technology transfer through FDI, whereas highly developed countries mainly benefit from FDI as a vehicle of global technology diffusion. Departing from this universal model, the book then investigates the impact of FDI on economic growth for the transition countries of Central and Eastern Europe. With the help of modern panel data econometrics it carries out the strongly awaited empirical evidence of a growth enhancing effect of FDI in the transition countries, and it explains for each country the actual growth contributions induced by FDI.